2019
DOI: 10.5123/s1679-49742019000100021
|View full text |Cite
|
Sign up to set email alerts
|

Mortalidade de pedestres em acidentes de trânsito no Brasil: análise de tendência temporal, 1996-2015*

Abstract: Objective: to analyze the mortality coefficient trend for road traffic accidents involving pedestrians in Brazil, by sex, age range and macro-region, between 1996 and 2015. Methods: this was an ecological time series study using data from the Ministry of Health's Mortality Information System (SIM); Prais-Winstein generalized linear regression was used to calculate annual percentage change. Results: pedestrian deaths corresponded to 26.5% of deaths due to road traffic accidents; mortality among pedestrians decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
0
8
0
7
Order By: Relevance
“…A capacidade de fiscalização dos órgãos do SNT, por exemplo, ainda é insuficiente nas três esferas de gestão do país 7 35 . Todas estas medidas provavelmente contribuíram para o declínio dos indicadores de mortalidade por ATT, principalmente nas regiões mais ricas do país e nas capitais, que contam com mais recursos e possivelmente conseguiram implantá-los de modo mais rápido e extenso em seus territórios 36 . Isso poderia explicar, também, as diferenças de mortalidade entre os meios de transporte, entre as cidades capitais e não capitais e entre as macrorregiões.…”
Section: Discussionunclassified
“…A capacidade de fiscalização dos órgãos do SNT, por exemplo, ainda é insuficiente nas três esferas de gestão do país 7 35 . Todas estas medidas provavelmente contribuíram para o declínio dos indicadores de mortalidade por ATT, principalmente nas regiões mais ricas do país e nas capitais, que contam com mais recursos e possivelmente conseguiram implantá-los de modo mais rápido e extenso em seus territórios 36 . Isso poderia explicar, também, as diferenças de mortalidade entre os meios de transporte, entre as cidades capitais e não capitais e entre as macrorregiões.…”
Section: Discussionunclassified
“…24 Consequently, improving road safety for pedestrians is substantial, as it can be a representative element of the population's quality of life. 25 In relation to the mortality profiles found, important differences were observed between municipalities with high, moderate, and low population density when compared to those with very high population density. Contrary to our findings, previous evidence has shown that population density has been inversely correlated with the number of deaths due to this cause.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, pedestrians aged at least 60 years old present approximately 9.6 and 4.2 more risks of dying than people aged 0-19 and 20-59 years, respectively. 25 Among other reasons, the risk derives from the existence of a traffic environment that is essentially dangerous and challenging for pedestrians and cyclists. 24 Consequently, improving road safety for pedestrians is substantial, as it can be a representative element of the population's quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Por fim, antes da Lei Seca a maior porcentagem de acidentes estava na categoria "outros acidentes de transporte terrestre" isso pode ter ocorrido devido a uma falha nos registros uma vez que o V80-V89 representa um inadequado registro dos veículos envolvidos no acidente (Campos et al, 2016). Após a Lei, talvez por melhor registro do CID e por outros motivos que serão abordados, a maior porcentagem migrou para a categoria pedestre traumatizado em um acidente de transporte (V01-V09), uma vez que caminhar é uma atividade diária popular entre a maioria das pessoas, independentemente de seu principal meio de transporte, sobretudo nos países de baixa e média renda, seja por questão de necessidade ou opção, existe grande número de pedestres expostos aos riscos do trânsito contribuindo para essa porcentagem (Fernandes & Boing, 2019).…”
Section: Resultsunclassified